The Impact of Generative Artificial Intelligence on Mental Health: Opportunities, Challenges, and Ethical Concerns - Sivanjali.V Sivanjali.V; Aryananda Ms; Abhirami Anilkumar; Nimisha Prakash (International Journal of Technology and Emerging Research, 2026)
Mental health conditions are one of the most pressing public health issues globally, impacting people of all ages and making it difficult for people to operate in health care systems around the world. As Generative Artificial Intelligence (GenAI) evolves quickly, it offers novel solutions for mental health care, like AI-powered chatbots, virtual assistants, emotion recognition systems, and personalized digital support platforms. This paper is an analysis of recent studies on the use of generative AI in mental health care which will compare the advantages, drawbacks, and ethical considerations of generative AI. The studies reviewed suggest that AI tools can help with greater accessibility of mental health supports, offer around-the-clock support, increase self-awareness, and decrease loneliness through personalized interactions. However, there are a number of issues to contend with: emotional reliance on AI companions, misinformation, privacy and security concerns, algorithmic bias, and a lack of clinical validation. This paper highlights insights from various studies on the current impact of Generative AI on mental health care and pinpoints areas where research is currently missing. The analysis recommends that Generative AI can revolutionize mental care but can't be a direct substitute for mental health professionals. Moving forward, it is crucial to promote responsible implementation of AI, ethical guidelines, transparency, and robust regulations to maintain safe and reliable mental health care services. Keywords: mental health; Ethical AI; emotion detection; Privacy; Generative Artificial Intelligence; AI Chatbots; Digital Healthcare; Mental Healthcare